Numerical analysis of factors causing long-term trends and annual variations of sulfur and nitrogen deposition amount in Japan from 2000 to 2020 - Satoru Chatani; Hikari Shimadera; Kyo Kitayama; Kazuya Nishina (Asian Journal of Atmospheric Environment)
Abstract The deposition of sulfur and nitrogen from the atmosphere to the ground surface is harmful to ecosystems. This study performed long-term air quality simulations to quantify the influences of factors, including anthropogenic emissions in Japan, meteorological fields, transboundary transport, and volcanic emissions, on the long-term trends and annual variations in sulfur and nitrogen deposition in Japan from 2000 to 2020. The air quality simulations performed well in reproducing the long-term trends and annual variations in the wet deposition amount, whereas the simulated dry deposition amount may contain larger uncertainties. The decreasing trends in sulfur deposition were statistically significant during the entire study period (2000–2020) in most of Japan. They were caused by the reduction of anthropogenic SO2 emissions in Japan and China, which was accomplished by the implementation of stringent emission controls, as well as a gradual decrease in SO2 emissions from the Miyakejima volcano, which erupted in 2000. No significant decreasing trends were found in nitrogen deposition in Japan during the first half of the study period (2000–2010). Decreases caused by the reduction in anthropogenic NOx emissions in Japan were compensated for by increases caused by increasing NOx emissions in China and changes in the gas-aerosol partitioning of nitrates instead of sulfates. The decreasing trend in nitrogen deposition in Japan became statistically significant during the second half of the study period (2010–2020) after anthropogenic NOx emissions started to decline in China. Meteorological fields primarily influenced annual variations in the amount of nitrogen deposition. This study reveals that long-term air quality simulations are useful for quantifying the influences of various factors on long-term trends and annual variations in sulfur and nitrogen deposition. Graphical Abstract